Hard Carbon Microspheres: Potassium‐Ion Anode Versus Sodium‐Ion Anode. Issue 3 (30th November 2015) - Jian, Zelang; Xing, Zhenyu; Bommier, Clement; Li, Zhifei; Ji, Xiulei
Abstract : Hard carbon microspheres (HCS) exhibit a highly reversible capacity of 262 mAh g −1 for K‐ion batteries. They present a superior rate capability for K‐ions to Na‐ions, where at 2C, HCS/K cells deliver 190 mAh g −1 in contrast to 97 mAh g −1 from HCS/Na cells. It is determined that the K‐ion diffusion coefficient of HCS is higher than that of Na‐ions.